JURNAL ILMU KESEHATAN JURNAL ILMU KESEHATAN STIKES DUTA GAMA KLATEN - maryanti S.SiT.,M.Kes (STIKES DUTAGAMA KLATEN, 2022)
Background: Perineal rupture is a tear that occurs in the perineum during labour. The highest cause of maternal death is bleeding, one of the causes of which is perineal rupture with an incidence rate of 16%.Research Objectives: To analyze the factors that influence the incidence of perineal rupture in women giving birth based on previous studies.Research Methods: This study used the Scoping Review method with various references, research journal searches were conducted from several databases such as Google Scholar, Science Direct and Pubmed with related keywords, such as "Factors" OR "Mother" OR "Perineum" OR "Rupture" OR “maternity”. While the search used Indonesian with the chosen keywords, namely "Factors that influence perineal rupture", the results obtained from 7 research journals from the 2017 - 2021 timeframe matched the mix of inclusion and exclusion.Research Results: The results obtained from 7 research journals show that the factors that influence perineal rupture in women giving birth are:Conclusion: Factors that influence perineal rupture in birthing mothers include; Parity factor, delivery distance, newborn weight, pushing technique factor, perineal mass factor.